A political corrida. Spanish-Catalan parallels - Husar, Wioletta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Corrida de tores, as an important component of Spanish culture, has also been the subject of a dispute between the aficionados (supporters of the corrida) and the antitaurinos (opponents of the corrida) for centuries. Naturally, the spectacle has become an object of interest for researchers not only in the socio-cultural context, where it is becoming a spectacle full of artistry, accompanied by great emotions, or a tradition in some aspects resembling the Fiesta Nacional, but also becoming increasingly important on the political, moral and ethical level.
Keywords: Catalan-Spanish conflict; corrida de toros; Catalanism; Catalan independency; banning of corrida